Headache attributed to TMD Is Associated With the Presence of Comorbid Bodily Pain: A Case‐Control Study. Issue 10 (4th September 2018) - Vivaldi, Daniela; Di Giosia, Massimiliano; Tchivileva, Inna E.; Jay, Gary W.; Slade, Gary D.; Lim, Pei F.
Abstract : Headache attributed to temporomandibular disorders (TMDH) is defined as a secondary headache by the International Classification of Headache Disorders 3rd edition (ICHD‐3). Objective: The objective of this case‐control study is to investigate the phenotypic characteristics of chronic TMD with and without TMDH. We hypothesize that chronic TMD with TMDH is associated with increased number of bodily pain conditions, more painful sites in the head and neck region, and greater TMD pain intensity. Methods: This is a retrospective cross‐sectional review of the medical records of consecutive patients who sought treatment at the University of North Carolina Orofacial Pain Clinic between 2013 and 2014. The inclusion criterion was a diagnosis of myalgia or arthralgia according to the Research Diagnostic Criteria for Temporomandibular Disorders. In addition, cases had a diagnosis of TMDH according to the ICHD‐3 criteria. Data on the presence and the number of self‐reported bodily pain conditions (such as fibromyalgia and low back pain), pain intensity, number of painful sites in the head and neck upon palpation, and TMD pain onset were analyzed. Results: A total of 295 records were reviewed. Thirty‐four (29.3%) patients fulfilled inclusion criteria for cases (TMD+TMDH) and 82 (70.7%) for controls (TMD−TMDH). Cases reported greater number of bodily pain conditions than controls, with a mean of 1.97 ± 1.50 and 1.26 ± 1.28 of bodily pain conditions, respectively ( P  = .012, OR = 1.43 [95% CI 1.07−1.92]). In fact, 55.9% of cases reported at least 2 comorbid pain conditions compared to 37.8% controls ( P  = .044). Compared to controls (8.65 ± 5.32), cases (13.05 ± 4.46) exhibited greater number of painful sites upon palpation in the head and neck region ( P  < .0001, OR = 1.18 [95% CI 1.09−1.30]), and greater TMD pain intensity, with a mean of 6.00 ± 2.17 for cases and 5.09 ± 2.14 for controls ( P  = .041, OR = 1.22 [95% CI 1.01−1.47]). Conclusion: In a population of patients with chronic TMD seeking pain management, TMDH was significantly associated with an increased number of self‐reported bodily pain conditions, a greater number of painful sites in the head and neck regions, and higher TMD pain intensity.